Single phase rectifier controlled using pic / Muzamir Syah Muslim - Muslim, Muzamir Syah (2009)
This project report presents to design high switching frequency rectifier controlled using PIC. The project will resolve harmonic problem by providing more reduction on harmonic content that created by nonlinear device. PIC acts as the controller to the rectifier. This project is concern on the AC side in term of harmonic. In the proposed work, MOSFET is used as switching device. It is because of it appreciable current carrying, off-state voltage blocking capability and low on-state voltage drop. Other than that, MOSFET require simpler gate requirements and higher positive temperature coefficient. A simple yet effective scheme for improving the power factor and waveshape of input current drawn by a single phase bridge rectifier is presented. A rectifier with filter capacitor draws current from the supply discontinuously, in short pulses. The simulated results reveal that the harmonic content of the scheme presented is few at lower frequency and shifted up to higher frequency.